Variation in biological status among Polish males and underlying socio-economic factors - Kaczmarek, Maria; Skrzypczak, Magdalena (Anthropological Review, 2008)
The main purpose of this study was to evaluate the socio-economic and lifestyle factors associated with biological status of Polish men. Data were collected during a cross-sectional survey carried out in Poznań and several localities in Western Poland, between 2000 and 2002. The sample consisted of 2509 men ranging from 30 to 90 years of age. Biological status was expressed in terms of functional-biological age (BA) computed as a composite z-score of 11 biomarkers according to the method proposed by Borkan and Norris [1980a], and physiological reserve index (PR) developed by Goffaux et al. [2005]. The average biological age profiles (BAP) were compared in several subgroups of participants. The subgroups were categorized based on demographic, socio-economic and lifestyle characteristics. It was found that values of systolic and diastolic blood pressure, BMI, physical and emotional aging indicators and perceived satisfaction with life were significantly associated with most of the study factors, except for smoking habit and education level. The multivariate logistic regression models revealed that two factors, financial situation and physical activity, were significantly associated with the physiological reserve index estimation. The study confirmed the role of the socio-economic and lifestyle factors likely to play in men's biological status and aging rates.